2015
DOI: 10.1039/c5ta05280g
|View full text |Cite
|
Sign up to set email alerts
|

High proton conductivity in cyanide-bridged metal–organic frameworks: understanding the role of water

Abstract: Supplementary Information (ESI) available: IR, PXRD, TGA and proton conductivity analysis for the as-synthesized NdMo−MOF and its activated forms at 80 °C, 130 °C and 150 °C, respectively. SeeWe investigate and discuss the proton conductivity properties of the cyanide-bridged metal-organic framework (MOF) [Nd(mpca)2Nd(H2O)6Mo(CN)8]·nH2O (where mpca is 5−methyl−2−pyrazinecarboxylate). This MOF is one of an exciting class of cyanide-bridged materials that can combine porosity with magnetism, luminescene, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…Moreover, they are environmentally friendly and have excellent biocompatibility, therefore they are widely employed to make smart multifunctional materials. [44] We have also demonstrated that these materials retain their structural integrity during multiple dehydration/hydration cycles. [37][38][39][40] A few examples of CDs@MOFs composites were reported so far.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Moreover, they are environmentally friendly and have excellent biocompatibility, therefore they are widely employed to make smart multifunctional materials. [44] We have also demonstrated that these materials retain their structural integrity during multiple dehydration/hydration cycles. [37][38][39][40] A few examples of CDs@MOFs composites were reported so far.…”
Section: Introductionmentioning
confidence: 73%
“…The most suitable method is the transmission electron microscopy (TEM). The bands in the range of 1550-1700 cm -1 , at 1500 cm -1 and 1100 cm -1 are the characteristic peaks of the EuW-MOF structure [44,45] and they indicate that the MOF framework is retained upon CDs uptake. [21] Fortunately, the reversibility of the dehydration-rehydration process provides the possibility to iden-tify the relative location of CDs within the MOF framework using photoluminescence measurements.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Pseudo-activation energies (Ea) were calculated by fitting the conductivity data to the Vogel−Tamman−Fulcher (VTF) equation ( Figure S13 ) [ 42 ], which is widely used for non-Arrhenius polymeric ion conductors. The non-Arrhenius behavior has been already described for other MOFs, although is not fully understood [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%